AI in higher education (Discourse of Law and Administration, 2025)
The ongoing digital transformation is affecting all economic, social and societal systems. The use of AI tools as assistants in everyday life is becoming increasingly popular. The presence of artificial intelligence is beginning to be noticed in higher education. Not only does it modernise it, but it can also contribute to building a more equitable and accessible education system for all. Freedom in the use of various IT tools, including content and image generators, is in line with the openness of both science and teaching, which should promote diversity of sources and content. The traditional role of education is to prepare students for life in the future. Universities should therefore take into account the growing importance of artificial intelligence in everyday life and actively incorporate it into the teaching process in order to prepare students to use these tools skilfully both in their professional and personal lives. It is worth emphasising that issues related to the use of artificial intelligence, both by lecturers and students, should be regulated by law. It should become mandatory to indicate the use of a content, image or sound generator each time, because the work created in this way is not entirely the work of the person who used the tool.
Keywords: artificial intelligence; higher education; etics